A quantitative content analysis of sexual harassment news: comparison of Daily Jang and Berita Harian newspaper - Hilal Fatima, .; Ahmad Ghazali, Akmar Hayati; Bukhari, Urwa (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2024)
Both Malaysian and Pakistani societies have been reported to have issues with sexual harassment, as indicated by victims and media sources. The media presentation of sexual harassment was observed in Daily Jang and Berita Harian newspaper by using the method of Content Analysis. The portrayal of sexual harassment issues in news coverage is an essential part of bringing awareness. The current study has focused to do a comparison of Sexual harassment news published between a Pakistani and a Malaysia newspaper to understand the differences and similarities in the pattern of news coverage. A total of 194 and 151 sexual harassment news respectively, were selected by defined coders, with the time frame of the year 2016. The chi-square test was applied to understand the significant difference between the amount of news in both newspapers. Inter-coder reliability was done to identify the agreement between coders. In the results of structural attributes Daily Jang and Berita Harian did not give prominence to sexual harassment and did not elevate awareness through news coverage. Even though, the negligence of the media and government is the similarity between the two countries. Both countries have this social problem but they do not have any agenda or policy to handle or control it. According to content attributes, most of the coverage was based on sensitization. However, Berita Harian had published a bit of educational and awareness content as compared to Daily Jang which was good but not enough for the betterment of society.